2014
DOI: 10.1021/es404705d
|View full text |Cite
|
Sign up to set email alerts
|

Does Water Content or Flow Rate Control Colloid Transport in Unsaturated Porous Media?

Abstract: Mobile colloids can play an important role in contaminant transport in soils: many contaminants exist in colloidal form, and colloids can facilitate transport of otherwise immobile contaminants. In unsaturated soils, colloid transport is, among other factors, affected by water content and flow rate. Our objective was to determine whether water content or flow rate is more important for colloid transport. We passed negatively charged polystyrene colloids (220 nm diameter) through unsaturated sand-filled columns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 67 publications
2
39
1
Order By: Relevance
“…transport of colloids, radioactive waste, bacteria, etc. through unsaturated soils (vadose zone) [117,127,128] or (thermal, electrical, etc.) conductivities in packed beds for technological uses [57,129].…”
Section: Equilibrium Interparticle Distancementioning
confidence: 99%
“…transport of colloids, radioactive waste, bacteria, etc. through unsaturated soils (vadose zone) [117,127,128] or (thermal, electrical, etc.) conductivities in packed beds for technological uses [57,129].…”
Section: Equilibrium Interparticle Distancementioning
confidence: 99%
“…The variation of IS under natural conditions (e.g., rain or irrigation) does not always show a decreasing trend, thus, a single study only relating to IS reduction effect on particle mobilization and transport in soil is not sufficient. As regard to FR perturbation, most of literatures showed that particle release would be increased as FR increasing (Knappenberger et al 2014;Sasidharan et al 2014), whereas some have interesting and unique results varies from most of literatures. Tosco et al (2012) pointed that FR did not significantly influence the particle deposition at low IS, when particle deposition rates were low.…”
Section: Introductionmentioning
confidence: 96%
“…Colloidal particles (1 nm to 10 μm) can act as important transport vectors of contaminants in soil system (Bin et al 2011;Knappenberger et al 2014;Murali et al 2014). With a high specific surface and mobility, colloidal particles always provide a rapid transport pathway for the sorbed contaminants thereby facilitating the transport of contaminants in the soil (Zhu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations